Aqueous extracts from Uncaria tomentosa (Willd. ex Schult.) DC. reduce bronchial hyperresponsiveness and inflammation in a murine model of asthma. (23rd May 2018) - Azevedo, Bruna Cestari; Morel, Lucas Junqueira Freitas; Carmona, Fábio; Cunha, Thiago Mattar; Contini, Silvia Helena Taleb; Delprete, Piero Giuseppe; Ramalho, Fernando Silva; Crevelin, Eduardo; Bertoni, Bianca Waléria; França, Suzelei Castro; Borges, Marcos Carvalho; Pereira, Ana Maria Soares
Abstract: Ethnopharmacological relevance: Uncaria tomentosa (Willd. Ex Schult) DC is used by indigenous tribes in the Amazonian region of Central and South America to treat inflammation, allergies and asthma. The therapeutic properties of U. tomentosa have been attributed to the presence of tetracyclic and pentacyclic oxindole alkaloids and to phenolic acids. Aims of the study: To characterize aqueous bark extracts (ABE) and aqueous leaf extracts (ALE) of U. tomentosa and to compare their anti-inflammatory effects. Materials and methods: Constituents of the extracts were identified by ultra performance liquid chromatography-mass spectrometry. Anti-inflammatory activities were assessed in vitro by exposing lipopolysaccharide-stimulated macrophage cells (RAW264.7-Luc) to ABE, ALE and standard mitraphylline. In vivo assays were performed using a murine model of ovalbumin (OVA)-induced asthma. OVA-sensitized animals were treated with ABE or ALE while controls received dexamethasone or saline solution. Bronchial hyperresponsiveness, production of Th1 and Th2 cytokines, total and differential counts of inflammatory cells in the bronchoalveolar lavage (BAL) and lung tissue were determined. Results: Mitraphylline, isomitraphylline, chlorogenic acid and quinic acid were detected in both extracts, while isorhyncophylline and rutin were detected only in ALE. ABE, ALE and mitraphylline inhibited the transcription of nuclear factor kappa-B in cell cultures, ALE and mitraphylline reduced the production of interleukin (IL)−6, and mitraphylline reduced production of tumor necrosis factor-alpha. Treatment with ABE and ALE at 50 and 200 mg kg −1, respectively, reduced respiratory elastance and tissue damping and elastance. ABE and ALE reduced the number of eosinophils in BAL, while ALE at 200 mg kg −1 reduced the levels of IL-4 and IL-5 in the lung homogenate. Peribronchial inflammation was significantly reduced by treatment with ABE and ALE at 50 and 100 mg kg −1 respectively. Conclusion: The results clarify for the first time the anti-inflammatory activity of U. tomentosa in a murine model of asthma. Although ABE and ALE exhibited distinct chemical compositions, both extracts inhibited the production of pro-inflammatory cytokines in vitro. In vivo assays revealed that ABE was more effective in treating asthmatic inflammation while ALE was more successful in controlling respiratory mechanics. Both extracts may have promising applications in the phytotherapy of allergic asthma. Graphical abstract: